A review of personalised e-learning: Towards supporting learner diversity - O'DONNELL, EILEEN; SHARP, MARY; WADE, VINCENT (My University, 2015)
The realisation of personalised e-learning to suit an individual learner's diverse learning needs is a concept which has been explored for decades, at great expense, but is still not achievable by non-technical authors. This research reviews the area of personalised e-learning and notes some of the technological challenges which developers may encounter in creating authoring tools for personalised e-learning and some of the pedagogical challenges which authors may encounter when creating personalised e-learning activities to enhance the learning experience of their students. At present educators who wish to create personalised e-learning activities require the assistance of technical experts who are knowledgeable in the area. Even with the help of an expert the creation of personalised e-learning activities still remains a complex process to authors who are new to the concept of tailoring e-learning to suit learner diversity. Before the successful utilisation of adaptive authoring tools can be realised, academic authors need to learn how to effectively use these tools. All learners come to education with a diverse set of characteristics; educators need to decide which learner characteristic(s) they wish to focus on addressing through the use of personalised e-learning activities. Further investigation, evaluation and analyses of authoring tools is required before personalised e-learning to support learner diversity can be achieved by many academics. Research members of the AMAS (2013) project team are currently involved in developing an authoring tool for adaptive activities for e-learning.
PUBLISHED
Keywords: cademics, Adaptive Technologies, Authoring Tools, Educators, E-Learning, Higher Education, Learner Diversity, Personalised E-Learning, Personalised E-Learning Activities, Role Playing, Students, User Profiles; User Profiles; Students; Role Playing; Personalised E-Learning Activities; Personalised E-Learning; Learner Diversity; Higher Education; E-Learning; Educators; Authoring Tools; Adaptive Technologies; Academics; Creative Technologies; Intelligent Content & Communications